Pelatihan Kegiatan Penelitian dan Penulisan Karya Ilmiah bagi Guru Madrasah Aliyah Negeri 3 Lombok Tengah - Muhali Muhali; Muhammad Asy’ari; Saiful Prayogi; Taufik Samsuri; I Wayan Karmana; I Ketut Sukarma; Baiq Mirawati; Laras Firdaus; Hunaepi Hunaepi (Universitas Prof. Dr. Hazairin, SH, 2019)
Training on Research Activities and Scientific Writing for Madrasah Aliyah Negeri 3 Lombok Tengah Teachers The purpose of this community service was to improve the ability of teachers to conduct research and publish a research article in a national scientific journal. This program was implemented through a series of activities using in-service training (IST) and on-service training (OST) methods. The andragogy approach was used in IST activities to improve the ability of teachers in analyzing the learning problems that can be raised as research problems; to convey the concept of research in general, especially classroom action research; and to write a scientific article. OST activities are intended to assist the teachers in conducting research activities, writing research reports and scientific articles and publishing scientific journals. The results of IST activities illustrated the situation of Madrasah Aliyah Negeri 3 Lombok Tengah teachers that most teachers had been able to analyze problems that can be raised as the main problems in research activities; the teacher had a good understanding of the concept of classroom action research, design, instruments, and analysis of research data; the teacher was able to understand the concepts and techniques of writing research reports and scientific articles; and the teacher had been able to understand the concepts and techniques of publishing articles in national scientific journals. OST results indicated that teachers had the potential to develop themselves in conducting research and producing scientific papers. During the implementation of community service activities, the teacher consistently followed the activities well. The resulting scientific work could be categorized as good, and generally, met the criteria of scientific writing.